The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1038/s41598-020-65814-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on influencing factors and mechanism of removal of Cr(VI) from soil suspended liquid by bentonite-supported nanoscale zero-valent iron

Abstract: In order to clarify the mechanism and effect of bentonite-supported nanoscale zero-valent iron (nZVI@Bent) on Cr(VI) removal in soil suspended liquid, nZVI@Bent was prepared by liquid-phase reduction method in this research. A number of factors, including the mass ratio of Fe 2+ to bentonite during preparation of nZVI@Bent, nZVI@Bent dosage, soil suspended liquid pH value and reaction temperature were assessed to determine their impact on the reduction of Cr(VI) in soil suspended liquid. The nZVI@Bent was char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Various tests were performed to evaluate the remediation effect of Cr(VI)-contaminated soil from different aspects. The Cr(VI) will adsorb on nZVI, through the surface pores and oxygen-containing functional groups, and then react directly with the surface to reduce to Cr(III), whereas nZVI is oxidized to Fe 2+ and indirectly reduced with Cr(VI) [66]. For example, toxicity characteristic leaching procedure is used to examine the leaching ability of Cr, and the immobilization and bioaccumulation of Cr in the improved soil are discussed through in vitro and plant experiments [67].…”
Section: Remediation Of Cr(vi)contaminated Soil By Nzvimentioning
confidence: 99%
See 4 more Smart Citations
“…Various tests were performed to evaluate the remediation effect of Cr(VI)-contaminated soil from different aspects. The Cr(VI) will adsorb on nZVI, through the surface pores and oxygen-containing functional groups, and then react directly with the surface to reduce to Cr(III), whereas nZVI is oxidized to Fe 2+ and indirectly reduced with Cr(VI) [66]. For example, toxicity characteristic leaching procedure is used to examine the leaching ability of Cr, and the immobilization and bioaccumulation of Cr in the improved soil are discussed through in vitro and plant experiments [67].…”
Section: Remediation Of Cr(vi)contaminated Soil By Nzvimentioning
confidence: 99%
“…In the experiment of nZVI@Bent materials mentioned above, it is found that with the increasing reaction temperature, the removal rate of Cr(VI) in soil solution by nZVI@Bent presents an ascending trend. The specific reason is that after the temperature rises, the energy in the reaction system increases correspondingly; thus, the number of reaction molecules increases and the reaction rate accelerates [66].…”
Section: Cr(vi)mentioning
confidence: 99%
See 3 more Smart Citations